ĖTNOKONFESSIJALYĶ ĶARYM-ĶATYNASTAR: CHALYĶARALYĶ TA̋ŽIRIBE - Zatov, K.A. (Chabaršy. Dintanu serijasy, 2017)
Kazakhstan is a multi-ethnic and multi-confessional state, successfully created image of a peaceful and stable country, whose calling card was ethnic and religious tolerance. In the article the questions connected with formation of ethnoconfessional relations are considered. Consideration of state policy in the ethno-confessional sphere of Malaysia for the application of positive experience in the Republic of Kazakhstan. Problems of ethno-confessional development and strengthening of national-state unity occupy one of the central places in the public and political life of the country. The history of the multinational states of Asia has repeatedly proved the relevance of ethno-confessional issues and the need for its solution: the differences between multi-lingual, multi-ethnic, multi-religious communities often lead to an aggravation of the domestic political situation, and in cases - even to the disintegration of states. One of the most important components of the political process, sometimes complicating the socio-political situation in multinational and polyconfessional states are ethno-confessional relations.